(untitled) - Bezděková, Hana (Aura musica, 2015)
The system of school choirs on 15. elementary school in Plzeň allows to work in the choirs to children from I. to IX. classes. Choral work brings significant benefits to the personality development of children, but we can also name some negative site and technical difficulties. The measure may be, for example, the relationship of the choristers to contemporary music.
Keywords: the children's choir; the school choir; personality development; contemporary music